(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The term literature is a comprehensive term that typically refers to works that fall within theprimary genres of epic, play, lyric, novel, short story, and ode. Poetry is a form of written communicationthat utilises a distinct style and cadence to convey the writer’s concepts and perspectives to theaudience. Due to the intricate employment of language in poetry, there exist numerous schools ofthought concerning the methods by which language can or ought to be employed in poetic contexts. Theincorporation of figurative language is a pivotal element in the comprehensive framework andconfiguration of a poem. The utilisation of language in a distinctive and often unorthodox manner hasled to William and Emily Dickinson being recognised as two of the most noteworthy poets of their time.The present investigation endeavours to examine the varieties of figurative language employed by poetsin their literary works. This study focuses on the life of Emily Dickinson and her utilisation of figurativelanguage in her poetry. Various figures of speech were employed, including but not limited to metaphor,personification, simile, hyperbole, and imagery.